Upstream process intensification and continuous manufacturing. (December 2018) - Chen, Chun; Wong, H Edward; Goudar, Chetan T
Abstract : Manufacturing process of biopharmaceuticals usually starts from culturing recombinant protein producing cells, predominately Chinese Hamster Ovary (CHO) cells, in bioreactors. Currently, fed-batch cell culture process is the most common upstream process method due to its operational simplicity and industrial familiarity. Intensified cell culture process, enabled by perfusion and other technologies, offers many benefits over traditional fed-batch cell culture mode. In this review, we discuss the current state-of-art for upstream cell culture process intensification with a focus towards continuous manufacturing. We also explore key technical drivers and their roles in steering towards a more cost-effective and flexible upstream biomanufacturing.